Interactive cinema : the ambiguous ethics of media participation - Hassapopoulou, Marina (Minneapolis : University of Minnesota Press, 2024)
"Interactive Cinema explores cinematic practices that work to transform what is often seen as a receptive activity into a participatory, multimedia experience. Combining cutting-edge theory with updated conventional film studies methodologies, Marina Hassapopoulou presses at the conceptual limits of cinema and offers an essential road map to the rapidly evolving landscape of contemporary media"--
Introduction: Interactive cinema, or the end of radical art? -- Sense and interactivity : bodily participation and exclusionary politics -- Collapsing and reconfiguring borders through interactivity -- Automation and non-/beyond-human interactivity -- Interactivity as ethics : deviant paradigms of identification in procedural spectatorship -- Afterword, or choose a different ending.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 13, 2024).
JSTOR
Keywords: Motion pictures -- Philosophy; Motion pictures -- Moral and ethical aspects; Visual perception in motion pictures; Motion picture audiences; Cinéma -- Philosophie; Cinéma -- Aspect moral; Perception visuelle au cinéma.; Cinéma -- Publics; PERFORMING ARTS / Film / History & Criticism; Film criticism; Critiques cinématographiques.